(3HGfJ SYGOs - (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eJHhd eJje EKQgG de jaO ecHhd s
(3BNQgG (B:s
(3dG jhbYhG GdWYf EdG ai fMhQge heGdge Yf MjGd GdehJ Jgdjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQgG eY gGeT JNejS GdHQOIs
(3fSNI KGfjIs
(3hQO CjVkG JMJ Qbe (B2185(3,(B2187s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs